Haploid doubling effect of waxy maize under different ecological environment (Bangladesh Journal of Botany, 2023)
The haploid seeds of five waxy maize hybrids, Jingkenuo 2000, Kennian 1, Wannuo 2000, Jikenuo 99 and Jikenuo 20, were treated with natural doubling and colchicine + DMSO chemical doubling. Results showed that the average doubling rates of Jingkenuo 2000, Wannuo 2000, Kennian 1, Jikenuo 20 and Jikenuo 99 were 0.30, 0.18, 0.53, 1.30 and 1.05%, respectively. The haploid doubling rates of Nanbin test site were higher than those of Shuangyang test site under different ecological environment. The haploid doubling rates of different doubling methods were different. Results showed that the doubling effect of needling growth point method was slightly better than that of soaking bud method, but the difference was very small, so it could be used flexibly. For different concentrations of colchicine solution, 0.08 mg/l solution had the best doubling effect on the haploid of waxy maize, with an average doubling rate of 7.96%, and the highest doubling rate of 10.70%.Bangladesh J. Bot. 52(2): 523-528, 2023 (June) Special